2017
DOI: 10.1590/1983-21252017v30n112rc
|View full text |Cite
|
Sign up to set email alerts
|

SELECTIVITY OF INSECTICIDES USED IN PEACH FARMING TO LARVAE OF Chrysoperla externa (NEUROPTERA: CHRYSOPIDAE) IN SEMI-FIELD CONDITIONS

Abstract: -The selectivity of five insecticides, regularly used in peach farming, was assessed for larvae of the predator Chrysoperla externa (Hagen) (Neuroptera: Chrysopidae) by means of bioassay in semi-field conditions. The bioassay was based on the counting of captured larvae after release in peach trees treated with the insecticides (% of active ingredient in spray liquid): deltamethrin (0.001), fenthion (0.050), phosmet (0.100), lufenuron (0.005) and malathion (0.200). Bait-cards with eggs of Anagasta kuehniella (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Integrated pest management has one of its basic components in the selectivity of insecticides, allowing the preservation of natural enemies. Studies on the selectivity of phytosanitary products recorded for coffee cultivation have been specifically developed in favor of predators (ROCHA et al, 2010;VILELA et al, 2010;CASTILHOS et al, 2017), and there is a lack of information about the effects on parasitoids.…”
Section: Methodsmentioning
confidence: 99%
“…Integrated pest management has one of its basic components in the selectivity of insecticides, allowing the preservation of natural enemies. Studies on the selectivity of phytosanitary products recorded for coffee cultivation have been specifically developed in favor of predators (ROCHA et al, 2010;VILELA et al, 2010;CASTILHOS et al, 2017), and there is a lack of information about the effects on parasitoids.…”
Section: Methodsmentioning
confidence: 99%
“…predator. Castilhos et al (2017) observed, under semi-field conditions, that insecticides (% a.i.) lufenuron (0.005) proved to be harmless (class 1); deltamethrin (0.001) and malathion (0.200) were slightly harmful (class 2), and fenthion (0.05) and phosmet (0.100) moderately harmful (class 3) to second instar larvae of C. externa.…”
Section: Soares a De F T And Carvalho G A 298mentioning
confidence: 98%
“…ere is thus a great need to find efficient and sustainable pest management strategies. e application of selective pest control based on pesticide selectivity tests is recommended in preserving these natural enemies as biological control instruments [7]. Selective pesticides promote the use of more satisfactory chemical insecticides, which in addition to being effective and satisfy certain criteria, they must not pose immediate or long-term risks to crops ecosystems.…”
Section: Introductionmentioning
confidence: 99%